Function and regulation of pob genes for 4-hydroxybenzoate catabolism in Agrobacterium tumefaciens - Xu, Nan; Wang, Wanyu; Cheng, Shuang; Zuo, Jiaojiao; Guo, Minliang (Applied and environmental microbiology, 2025)
Agrobacterium tumefaciens is a widely distributed environmental bacterium and a recognized phytopathogen. Phenolic acids influence the relationship between A. tumefaciens and plants. One of the most important phenolic acids found in soil is 4-hydroxybenzoate, which is generated by plants. Mutants defective in the atu4544 and atu4545 genes inhibit A. tumefaciens tumor development. The atu4544 -encoded enzyme, PobA, can metabolize 4-hydroxybenzoate, and the expression of its gene is positively regulated by the transcription factor encoded by atu4545 . The atu4545 gene is subject to negative autoregulation. The binding site of atu4545 is CGTGCGATGGTCGGATT . Dual regulation of regulators for phenolic acid catabolism may aid in the maintenance of appropriate quantities of phenolic compounds. These results clarify the pathogenic mechanisms of A. tumefaciens and broaden the understanding of the metabolic control mechanisms of phenolic chemicals.